Hydrodynamics of Bontang Seawaters: Its Effects on the Distribution of Water Quality Parameters - Ulung Jantama Wisha; Semeidi Husrin; Gegar Sapta Prasetyo (Marine Science Department Diponegoro University, 2016)
Bontang is a crowded with residential and industrial activities which produce heat waste into surrounding waters. This condition may cause environmental problems, and changes in water condition. Knowledge about dynamics of physic and chemical waters condition in Bontang city is very important as an effort to address environmental issues as part of coastal zone management and protection. The aim of this research is to understand hydrodynamic characteristics (tide and current) and the influence to distribution of physics and chemical in Bontang waters base on primary data (current and tide during one month, physics and chemicals waters data taken by in situ) and secondary data (bathymetry and tide forecasting). Hydrodynamic simulation is based on MIKE 21 and supported by CD-Oceanography and WR plot. The results show that the current is dominant move toward the Southwest and Northeast with current speed ranged from 0-0,22 m.s-1. The results of hydrodynamic simulation in the surface water show that the current move base on tide movement with current speed ranged from 0-0,24 m.s-1. The results of physic and chemical concentration is analysed by ArcGIS 10 to know spatial distribution of all parameters. Surface temperature ranged from 29-31,8oC, surface density ranged from 20-20,6 ppm, salinity ranged from 33,1-33,5 ppm, dissolve oxygen concentration ranged from 0,078-0,11 ppm. Distribution of all physic and chemical parameters is influenced by current and tide movement. Keywords: current, numerical model, water quality, Bontang waters